2021
DOI: 10.1186/s12866-021-02295-y
|View full text |Cite
|
Sign up to set email alerts
|

Skin microbiota dynamics following B. subtilis formulation challenge: an in vivo study in mice

Abstract: Background Modulating the microbiota is a leading-edge strategy for the restoration and maintenance of a healthy, balanced environment. The use of health-promoting bacteria has demonstrated some potential benefits as an alternative for skin microbiota intervention. Here, we investigate the manipulation of mice skin microbiota using B. subtilis incorporated into a supportive Pluronic F-127 hydrogel formulation. The formula plays an important role in delivering the bacteria to the desired action … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In agreement with this observation, other work analyzing the shift in mouse ear microbiota composition during and after B. subtilis administration found that there were shifts in the microbiota composition during administration of the bacteria, but the microbiota composition was similar to that of the untreated control group within a week after stopping administration of bacteria. 25 Starting with equal numbers of the representative skin microbiome species in this model, the relative steady state percentages predicted by the computational model qualitatively matched relative percentages of their genera identified from swabs of human forearm skin. 26 The computational model also predicted that a species with doubling time and carbon source utilization characteristics representative of B. subtilis could survive within an established community representing the skin microbiome for a little over half a day.…”
Section: Discussionmentioning
confidence: 84%
“…In agreement with this observation, other work analyzing the shift in mouse ear microbiota composition during and after B. subtilis administration found that there were shifts in the microbiota composition during administration of the bacteria, but the microbiota composition was similar to that of the untreated control group within a week after stopping administration of bacteria. 25 Starting with equal numbers of the representative skin microbiome species in this model, the relative steady state percentages predicted by the computational model qualitatively matched relative percentages of their genera identified from swabs of human forearm skin. 26 The computational model also predicted that a species with doubling time and carbon source utilization characteristics representative of B. subtilis could survive within an established community representing the skin microbiome for a little over half a day.…”
Section: Discussionmentioning
confidence: 84%
“…As FDA-approved polymer, the construction and biocompatibility of poloxamer 407 are proved in our study, in line with previous reports [ 33 ]. P407 were employed as carrier of microbiota-modulating agent like bacillus for skin infection treatment mainly due to its lower critical solution temperature, since it allows bacteria to grow inside the formula, prolong the retention of bacteria in the injection location without compromising bacteria's ability to produce and secret [ 46 ]. Therefore, we speculate P407 hydrogel could also prolong the preservation of FOLactis and be beneficial for secreting of fusion protein containing Flt3L and OX40L, which has been proved in follow-up experiment.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, alginate-derived hydrogels ionically crosslinked by Ca 2+ have been widely employed to construct living bacterial delivery systems due to their excellent cell compatibility and gentle gelation behaviors [ [47] , [48] , [49] , [50] ]. Thermogelling hydrogels have also been used in previous works to deliver living bacteria to their convenience during both the preparation of the bacteria-encapsulating hydrogel precursor solutions and in vivo administration [ 41 , [51] , [52] , [53] ]. However, the relatively high critical concentration and low mechanical strength of physical hydrogels are unfavorable for the exchange of substances and long-term bacterial survival during the treatment process.…”
Section: Hydrogels For the Delivery Of Living Bacteria Therapeuticsmentioning
confidence: 99%
“…Furthermore, the tunable mechanical properties and penetrability of this living bacterial agent increased its potential for antifungal applications. Moreover, their subsequent study revealed that B. subtilis in Pluronic F-127 has the capability to modulate the composition of the skin microbiota, which is beneficial for skin disease treatment [ 52 ].…”
Section: Recent Advances In the Use Of Hydrogels For Living Bacteria-...mentioning
confidence: 99%